Classroom Climate of first Year Students at a selected Secondary Vocational School after the Covid-19 Pandemic - Zelníčková, Helena; Válek, Jan; Sládek, Petr (R&E-SOURCE, 2023)
The paper addresses the issue of classroom climate after long-term online education in a selected vocational school. Long-term distance learning in the context of the Covid-19 pandemic has significantly affected the whole concept of education in the 2020/2021 school year. As a result of long-term distance learning, social bonding within classroom collectives has weakened, especially among first-year students at different school levels. In the research part of the article, the results of a research investigation at the Secondary vocational School of Informatics, Postal Administration and Finance in Brno are presented. The research was focused on the quality of the classroom climate of selected first-year technical and non-technical fields of study. The findings show Covid-19 had an impact on the environment of the school classrooms studied. The research was carried out after students returned to full-time teaching in June 2021 Mareš & Ježek (2012). The questionnaire was used to conduct the research investigation about School Classroom Climate.